2018
DOI: 10.1007/s11095-017-2282-4
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor-Loaded Nanoparticles with Enhanced Cytokine Metabolic Stability and Anti-Inflammatory Activity

Abstract: NanoLIF and CD11b-NanoLIF preserved the metabolic stability and biological activity of LIF in vitro. These results are promising to improve the therapeutic potential of LIF in treating neurodegenerative and inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Despite the lack of positive response to LIF, patients showed no side effects, confirming the promising use of LIF for systemic treatments. Moreover, a recent study designed and synthetised LIF-loaded and vectorised nanoparticles for the targeting of activated peripheral macrophages, which were able to decrease murine leukemic cell M1 proliferation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of positive response to LIF, patients showed no side effects, confirming the promising use of LIF for systemic treatments. Moreover, a recent study designed and synthetised LIF-loaded and vectorised nanoparticles for the targeting of activated peripheral macrophages, which were able to decrease murine leukemic cell M1 proliferation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, Stephanie et al successfully delivered Leukemia Inhibitory Factor (LIF) by fabricating poly(ethylene glycol)–poly(lactic acid) (PEG-PLA) polymer backbone polymeric nanoparticles (NanoLIF) and modified their surfaces with a CD-11b antibody (CD-11b-NanoLIF) to target peripheral-macrophages. The results indicated that the CD11-b-NanoLIF successfully targeted the activated peripheral-macrophages and significantly decreased inflammation by inhibiting M1-cell growth over 72 hrs as compared to the free LIF 176. In conclusion, polymeric nanoparticles either surface modified or naked could be an important strategy to treat AS and localized inflammatory disorders.…”
Section: Nanotechnology-based Treatment Approaches For Asmentioning
confidence: 88%
“…The latter is one of the major reasons why the delivery of cytokines is yet to be fully explored. Regardless, nanoparticles remain the most used vehicle for this purpose and many types have been studied that include sources such as polymeric [32,33], chitosan [14], gold [34], silica [35], magnetic [36] to liposomal [37,38] nanoparticles (Table 1). The cytokines can be encapsulated, adsorbed or conjugated into the nanocarrier system, and the nanometric size of these delivery systems increases the absorption of the drug by the cells, when compared to larger particles.…”
Section: Nanoparticles As Cytokine Delivery Systemsmentioning
confidence: 99%